Immune response to viscerotropic Leishmania: a comprehensive review - Lodi, Lorenzo; Voarino, Marta; Stocco, Silvia; Ricci, Silvia; Azzari, Chiara; Galli, Luisa; Chiappini, Elena (Frontiers in Immunology, 2024)
L. donovani and L. infantum infections are associated with a broad clinical spectrum, ranging from asymptomatic cases to visceral leishmaniasis (VL) with high mortality rates. Clinical manifestations such as post-kala-azar dermal leishmaniasis (PKDL) and visceral leishmaniasis-associated hemophagocytic lymphohistiocytosis-mimic (VL-associated HLH-mimic) further contribute to the diversity of clinical manifestations. These clinical variations are intricately influenced by the complex interplay between the host's immune response and the parasite's escape mechanisms. This narrative review aims to elucidate the underlying immunological mechanisms associated with each clinical manifestation, drawing from published literature within the last 5 years. Specific attention is directed towards viscerotropic Leishmania spp. infection in patients with inborn errors of immunity and acquired immunodeficiencies. In VL, parasites exploit various immune evasion mechanisms, including immune checkpoints, leading to a predominantly anti-inflammatory environment that favors parasite survival. Conversely, nearly 70% of individuals are capable of mounting an effective pro-inflammatory immune response, forming granulomas that contain the parasites. Despite this, some patients may experience reactivation of the disease upon immunosuppression, challenging current understandings of parasite eradication. Individuals living with HIV and those with inborn errors of immunity present a more severe course of infection, often with higher relapse rates. Therefore, it is crucial to exclude both primary and acquired immune deficiencies in patients presenting disease relapse and VLassociated HLH-mimic. The distinction between VL and HLH can be challenging due to clinical similarities, suggesting that the nosological entity known as VL-associated HLH may represent a severe presentation of symptomatic VL and it should be considered more accurate referring to this condition as "VL-associated HLH-mimic". Consequently, excluding VL in patients presenting with HLH is essential, as appropriate antimicrobial therapy can reverse immune dysregulation. A comprehensive understanding of the immune-host interaction underlying Leishmania infection is crucial for formulating effective treatment and preventive strategies to mitigate the disease burden.